Interaction of bacterial communities and indicators of water quality in shoreline sand, sediment, and water of Lake Michigan. (1st July 2020) - Nevers, Meredith B.; Byappanahalli, Muruleedhara N.; Nakatsu, Cindy H.; Kinzelman, Julie L.; Phanikumar, Mantha S.; Shively, Dawn A.; Spoljaric, Ashley M.
Abstract: Shoreline sand harbors high concentrations of fecal indicator bacteria (FIB) that may be resuspended into the water column through washing and resuspension. Studies have explored coastal processes that influence this sand-water flux for FIB, but little is known about how microbial markers of contamination or the bacterial community interact in the sand-water interface. In this study, we take a three-tiered approach to explore the relationship between bacteria in sand, sediment, and overlying water at three shoreline sites and two associated rivers along an extended freshwater shoreline. Samples were collected over two years and analyzed for FIB, two microbial source tracking (MST) markers ( Catellicoccus marimammalium, Gull2; Bacteroides HF183), and targeted metagenomic 16S rRNA gene analysis. FIB was much higher in sand than in water at all three sites. Gull2 marker was abundant in shoreline sand and water while HF183 marker was mostly present in rivers. Overall bacterial communities were dissimilar between sand/sediment and water, indicating little interaction. Sediment composition was generally unfavorable to bacterial resuspension. Results show that FIB and MST markers were effective estimates of short-term conditions at these locations, and bacterial communities in sand and sediment reflected longer-term conditions. Findings are useful for locating contamination sources and targeting restoration by evaluating scope of shoreline degradation. Graphical abstract: Image 1 Highlights: E. coli and gull microbial markers were higher in sand than in water. Bacterial communities in sand and sediment had limited overlap. Diversity of bacterial communities fluctuated in water more than in sediment. E. coli and microbial markers are dynamic and indicative of short-term conditions. Sand bacterial communities indicate long-term shoreline conditions.